2017
DOI: 10.18172/cig.3209
|View full text |Cite
|
Sign up to set email alerts
|

Across the Arid Diagonal: deglaciation of the western Andean Cordillera in southwest Bolivia and northern Chile

Abstract: ABSTRACT. Here we review published cosmogenic records of glaciation and deglaciation from the western cordillera of the arid subtropical Andes of northern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 56 publications
1
31
0
2
Order By: Relevance
“…5). Glaciers advanced in nearby parts of the southern Central Andes around this time, for example the Nevado de Chañi (24°S; Martini et al, 2017) and the Sierra de Quilmes (26°S; Zech et al, 2017), as well as farther north at the Chajnantor plateau (23°S; Ward et al, 2015;, Uturuncu volcano (22°S; Blard et al, 2014;Ward et al, 2017), and the Cordillera Huayhuash in Peru (10°S; Hall et al, 2009). We therefore infer that the M1 advance at the Sierra de Aconquija occurred within a more widespread wet period in the Central Andes, corresponding to the summer insolation maximum around 40-45 ka, during which the SASM was intensified.…”
Section: Moraine Unit M1mentioning
confidence: 99%
See 2 more Smart Citations
“…5). Glaciers advanced in nearby parts of the southern Central Andes around this time, for example the Nevado de Chañi (24°S; Martini et al, 2017) and the Sierra de Quilmes (26°S; Zech et al, 2017), as well as farther north at the Chajnantor plateau (23°S; Ward et al, 2015;, Uturuncu volcano (22°S; Blard et al, 2014;Ward et al, 2017), and the Cordillera Huayhuash in Peru (10°S; Hall et al, 2009). We therefore infer that the M1 advance at the Sierra de Aconquija occurred within a more widespread wet period in the Central Andes, corresponding to the summer insolation maximum around 40-45 ka, during which the SASM was intensified.…”
Section: Moraine Unit M1mentioning
confidence: 99%
“…Prior works identified anomalously old outliers on the grounds that they (i) sit far away from age clusters (e.g., Martini et al, 2017); (ii) violate the local stratigraphic order (e.g., Bromley et al, 2016;Ward et al, 2017;Zech et al, 2017); (iii) can be identified by statistical testing (e.g., Smith et al, 2005a,b;Jomelli et al, 2011);or (iv) by field observations that suggest a particular boulder is significantly older or was derived from hillslope debris (e.g., Martin et al, 2018).…”
Section: Nuclide Inheritancementioning
confidence: 99%
See 1 more Smart Citation
“…La evolución de éstos glaciares se corresponde con otros estudios para los Andes Centrales (Espizua 1999(Espizua , 2002(Espizua y 2004Moreiras et al, 2016) y en general en la cordillera de los Andes (Ackert, et al 2008;Glasser, et al 2008;Martinez et al, 2011;Martini et al, 2017;Rabassa et al, 2011;Ward et al, 2017;Zech et al, 2017;Vargo et al, 2018), habiéndose identificado en diversos depósitos morrénicos de los Andes Áridos los eventos del Último Máximo Glacial y el Tardiglaciar (Moreiras et al, 2016y Martini et al, 2017.…”
Section: Discussionunclassified
“…Las glaciaciones ocurridas durante el periodo Cuaternario, han modelado intensamente el relieve actual de la cordillera de los Andes (Ackert, et al 2008;Glasser, et al 2008;Martinez et al, 2011;Martini et al, 2017;Ward et al, 2017;Zech et al, 2017;Vargo et al, 2018). Durante el Pleistoceno (2,58 a 0,0117 Ma) y Holoceno (desde hace 11,700 ka antes del presente, BP) han ocurrido diversos eventos de descenso de temperatura y avances de los frentes de hielo glacial.…”
Section: Introductionunclassified